Septic shock is an independent risk factor for colistin-induced severe acute kidney injury: a retrospective cohort study - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2016)
Introduction: Colistin, a last-line therapeutic agent for the treatment of multidrug-resistance gram-negative infections, is limited in its use due to nephrotoxicity. This retrospective cohort study evaluates risk factors for colistin-induced severe acute kidney injury (AKI) in critically ill patients. Methods: Patients admitted to a university hospital ICU, were without pre-existing kidney injury, and received colistin therapy 72 or more hours were included. Patient demographics, the source of infection and outcome were collected. AKI was evaluated by using the RIFLE criteria. Risk factors for the development of AKI were analyzed via logistic regression analysis. Results: One-hundred and two patients were included in the study. The overall incidence of AKI was 77.5% (n=79), and that of severe AKI was 34.3% (n=35). On univariate analysis, age and septic shock correlated significantly with severe AKI patients (P=0.042, P=0.001, respectively). By multivariate logistic regression analysis, septic shock was the only independent risk factor for colistin-induced severe AKI (OR 8.580 [1.868-39.417]; P=0.006). Conclusions: A high incidence of colistin-induced AKI defined by RIFLE criteria is observed in critically ill patients. Septic shock is the only variable independently associated with severe AKI induced by colistin therapy.
Keywords: Colistin; acute kidney injury; septic shock; critically ill; CRITICALLY-ILL PATIENTS; GRAM-NEGATIVE BACTERIA; INTRAVENOUS COLISTIN; POLYMYXIN-B; NEPHROTOXICITY; MULTIRESISTANT; EPIDEMIOLOGY; PREDICTORS; OUTCOMES; THERAPY